THE STUDY OF MARKETING TURN OF REAL ESTATE INTERNET PLATFORM AND VALUE CHAIN RESHAPING - Zhiyong Liu; Supot Rattanapun (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The real estate platform playing an important role in sales cannot be used with essential links such as display, negotiation, transaction, and signing. As a result, the real estate sales process has lost its venue, resulting in real estate sales entering a frozen state. However, there are few in-depth studies to distinguish and verify the connection between the value chain between public health events-market-real estate-consumers and see the role of real estate in the chain and its response options. This study attempts to investigate the marketing of real estate Internet platforms. The research object of this article is limited to the Internet platform of real estate rather than public real estate companies. It mainly focuses on the marketing method of the platform and the value chain turns it reflects. It relies heavily on years of work experience and actual industry data, which are operability and feasibility. The results show the marketing method of the platform and the value chain and how they reflect each other. The result aims to deconstruct the value chain between public health events-market-real estate-consumers and to see the role of real estate in the chain and its response options.